PENGARUH GREEN ACCOUNTING, KEPEMILIKAN MANAJERIAL DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN (Studi Empiris Perusahaan Pertambangan yang Terdaftar di BEI Periode 2016- 2019) - Novita Aprilia Sari; Moh. Amin; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2021)
The research objective is to determine the effect of Green Accounting, Managerial Ownership and Good Corporate Governance on Company Performance in mining companies listed on the Indonesia Stock Exchange in 2016-2019. Using purposive sampling with a total of 28 sample companies obtained during the period 2016-2018. Using multiple linear regression in analyzing data. The results obtained: simultaneously green accounting, managerial ownership and good corporate governance have an effect on company performance. Partially, green accounting has no effect on company performance, managerial ownership has an effect on company performance and good corporate governance has an effect on company performance.Keywords: Green Accounting, Managerial Ownership, Good Corporate Governance, Company Performance.